Етична складова застосування штучного інтелекту при вирішенні інтелектуальних задач - Волобуєва, Д. С.; Губін, В. О. (ХНУРЕ, 2025)
Nowadays, artificial intelligence has become an integral part of our lives. Many companies are implementing it in their operations to enhance business efficiency. However, despite its numerous advantages, the widespread use of AI may threaten the role of humans in traditional professions and raise serious ethical concerns. This paper examines the key ethical aspects of artificial intelligence in solving intellectual tasks. The development of appropriate ethical standards for the use of modern information technologies will help ensure safety and the protection of fundamental human rights.
Keywords: вирішення інтелектуальних задач; етична складова